Actions to transform food systems under climate change: Drive social change for more sustainable decisions - Transforming Food Systems Under a Changing Climate Initiative (2020)
Transforming Food Systems Under a Changing Climate is an initiative that aims to identify high-priority actions for food systems to both adapt to climate change and reduce emissions, while not losing sight of the many other functions of, and challenges to, our food systems. The action described in this briefing is one of 11 transformative actions that should take priority. For a transformation in food systems to take place, behavioral change on a large scale is necessary, by producers and consumers alike. Social movements have the power to trigger transformation processes, for instance by promoting behavioral change by businesses by creating new social norms. At the same time, policies that encourage new behaviors can promote changes in consumer habits.